PERBEDAAN KUALITAS ROTI TAWAR DENGAN SUHU 30 °C DAN 50°C DALAM PELARUT RAGI KORAL - Mardiah, Anisah; Elida, Elida; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
This research is based on the absence of warm water temperature standard in coral yeast dissolution. The aim of this research is to analyze the difference of quality of fresh bread with temperature 30 ° C and 50 ° C in coral yeast solvent which include external quality (volume, shape, color) and internal quality (texture, flavor and taste). Types of pure experimental research (true experiment) with complete random design method and object of research that is fresh bread. Primary data types from 5 expert panelists by responding to organoleptic test format. Data were analyzed using different test (Ttest) to see the real difference between two treatments with a significant level of 0.50. The results of this study indicate that there is a significant influence on the quality of fresh bread include external quality (volume, neat shape, rectangular shape 8cm x10cm, skin color) and internal quality (texture of softness, elastic texture, pore smoothness texture, Pores, yeast scent, fragrant aroma, flavor) from both temperatures of 30 ° C (X1) and 50 ° C (X2), since Fcount> Ftable means ha accepted. The best results based on organoleptic test are X1 with temperature 30 ° C.Keywords: Bread Quality Differences, Temperature 30 ° C, and 50 ° C, Coral Corrg.